2020
DOI: 10.3389/fpsyt.2020.603933
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition and Social Cognition Predicting 1-Year Outcomes in First-Episode Psychosis

Abstract: Cognitive performance at illness onset may predict outcomes in first-episode psychosis (FEP), and the change in cognition may associate with clinical changes. Cognitive testing was administered to 54 FEP participants 2 months after entering treatment and to 39 participants after 1 year. We investigated whether baseline cognition predicted 1-year outcomes beyond positive, negative, and affective symptoms and whether the trajectory of cognition associated with clinical change. Baseline overall neurocognitive per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“… 2014 ; Fortgang, Srihari, & Cannon, 2020 ; Jurado & Rosselli, 2007 ; Lindgren et al . 2020 ). More longitudinal studies are required to gain more insight into the relationship between cognitive function and negative symptoms in FEP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2014 ; Fortgang, Srihari, & Cannon, 2020 ; Jurado & Rosselli, 2007 ; Lindgren et al . 2020 ). More longitudinal studies are required to gain more insight into the relationship between cognitive function and negative symptoms in FEP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between cognitive function and negative symptoms seems complex. Severe negative symptoms such as lack of motivation or decreased effort may impact cognitive performance but similarly, cognitive impairment could affect the manifestation of negative symptoms as more preserved cognitive function may be essential for the ability to plan, initiate, motivate and carry out daily activities (Beck, Himelstein, Bredemeier, Silverstein, & Grant, 2018;Fervaha et al 2014;Fortgang, Srihari, & Cannon, 2020;Jurado & Rosselli, 2007;Lindgren et al 2020). More longitudinal studies are required to gain more insight into the relationship between cognitive function and negative symptoms in FEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has lent support to the hypothesis of some overlap between negative and cognitive symptoms and highlighted the intricate interplay among cognition, negative symptoms, and functioning, with mixed findings in prior reports. In FEP patients, meta-analytic findings have demonstrated the substantial relationship of cognition with future psychosocial functioning, after accounting for negative symptoms [17], whereas a separate report found that the inclusion of negative symptoms in the analysis eliminated the predictive power of cognition for 1-year outcomes, underscoring the intersection between negative symptoms and cognition [25]. Moreover, some reports in CHR individuals have shown a predictive relationship between cognitive variables and functioning through the partial mediation of negative symptoms [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…No association was found between TMT-A and negative symptoms [24]. Another study which included measures from WAIS, the WMS, the TMT, verbal fluency, the tapping task, and the continuous performance test identical pairs found cognitive functions to be correlated inversely with negative symptoms but not with positive or affective symptoms one year after admission [25]. A third study, revealed that improvements over time in general cognitive function, working memory, and verbal learning were mediated by improvements in positive and negative symptomatology [26].…”
Section: Introductionmentioning
confidence: 96%